Adenylyl cyclase-cyclicAMP signaling in mood disorders: Role of the crucial phosphorylating enzyme protein kinase A - Yogesh Dwivedi (Dove Medical Press, 2008)
Yogesh Dwivedi, Ghanshyam N PandeyPsychiatric Institute, Department of Psychiatry, College of Medicine, University of Illinois at Chicago, Chicago, Illinois 60612, USAAbstract: Mood disorders are among the most prevalent and recurrent forms of psychiatric illnesses. In the last decade, there has been increased understanding of the biological basis of mood disorders. In fact, novel mechanistic concepts of the neurobiology of unipolar and bipolar disorders are evolving based on recent pre-clinical and clinical studies, most of which now focus on the role of signal transduction mechanisms in these psychiatric illnesses. Particular investigative emphasis has been given to the role of phosphorylating enzymes, which are crucial in regulating gene expression and neuronal and synaptic plasticity. Among the most important phosphorylating enzyme is protein kinase A (PKA), a component of adenylyl cyclase−cyclic adenosine monophosphate (AC−cAMP) signaling system. In this review, we critically and comprehensively discuss the role of various components of AC−cAMP signaling in mood disorders, with a special focus on PKA, because of the interesting observation that have been made about its involvement in unipolar and bipolar disorders. We also discuss the functional significance of the findings regarding PKA by discussing the role of important PKA substrates, namely, Rap-1, cyclicAMP-response element binding protein, and brain-derived neurotrophic factor. These studies suggest the interesting possibility that PKA and related signaling molecules may serve as important neurobiological factors in mood disorders and may be relevant in target-specific therapeutic interventions for these disorders.Keywords: protein kinase A, bipolar disorder, unipolar depression, CREB, BDNF, Rap-1